SYNTHESIS OF METHODS FOR PERFORMANCE EVALUATION OF FORWARDING SERVICE DELIVERY SYSTEM - Казак, В.; Кошляк, І. (Science-based technologies, 2010)
Currently freight — is one of the most important parts of the economy. The transport of goods is of great importance in the development and operation of any freight forwarding company. The company, as a complex economic system, with close-bahatop rofilnym interrelation of all its elements and parts requires a systematic approach through the account of correlations, the study of some economic objects as structural parts of complex systems.